The Improvement of Justice with the Aid of Science and Expert Witnesses - Orville W. Richardson (Washington University Law Quarterly, 1951)
Upon the premise that law evolves from facts, its quality as “correct” or “just” will vary with the quality of facts presented as “correct” or “true.” The need thus arises for better preservation, selection, testing, synthesis and presentation or proof of facts. Since the organization of knowledge is the aim of science, lawyers and courts should be and are inclined to invoke the aid of science and its men of learning and experience in the process of gathering and presenting facts in court. Without them we would be forced to rely upon the naive, uncritical, superstitious and speculative observations of lay witnesses and jurors. In an ideal system, the scientist and expert witness would be the most honored of men, and upon the supposition that they deal with immutable laws of the physical world, we would find the jury largely displaced by them.
Keywords: Administration of justice